The Relationship Between Academic Supplies and Academic Performance - Malissa Harris; Celia Suarez; Rylei Jaramillo; Ebony Hall; Felicia L Murray (Undergraduate Research Journal for the Human Sciences, 2023)
Many students attending college lack the resources for academic supplies to help them achieve academic success. This study was informed by Walberg’s Theory of Educational Productivity and Maslow’s Hierarchy of Needs to aid in the understanding of how access to academic supplies affects academic achievement as well as graduation and retention rates. This research focused on the access to academic supplies and a student’s academic performance. The research was a mixed methods approach with a randomized sample of 75 participants. A hard copy survey was distributed in the highest trafficked areas on a college campus. In addition to the demographic questions, the participants answered questions about their academic performance and access to academic supplies. The data was analyzed through quantitative analysis and qualitative analysis examining the open-ended questions by identifying codes, categories, and collapsing into sizeable themes. Although the quantitative analyses revealed no significant relationship between academic supplies and academic performance, there were findings that supported differences between first-generation students. More than half of the participants who identified as a first-generation student did not know there were free resources available compared to non-first-generation student participants. The crosstabulation revealed students indicated the reason they received below a C in a course was due to textbooks, access codes, and other limited accessibility issues. African American students had the largest percentage within their group who received below a C due to not having access to textbooks (60%; n=6) compared to 13.2% (n=7) of Whites and 12.5% (n=1) of Hispanic/Latinx students. The qualitative analyses revealed three major outcomes: 1) textbooks are expensive, 2) textbooks are sold out quickly and 3) financial aid does not flow into students' accounts until later in the semester. The research provides awareness and informs alternative cost-efficient academic materials to improve student success.
Keywords: Academic Supplies; Academic Materials; Academic Performance; First generation students; Academic Achievment